2021
DOI: 10.1183/23120541.00334-2021
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and economic burden of bronchiectasis requiring hospitalisation in Singapore

Abstract: Background and objectiveLittle is known about the epidemiology and cost of bronchiectasis in Asia. This study describes the disease burden of bronchiectasis in Singapore.MethodsA nationwide administrative dataset was used to identify hospitalisations with bronchiectasis as a diagnosis. Population statistics and medical encounter data were used to estimate the incidence, mortality, prevalence and direct medical costs associated with hospitalisation-requiring bronchiectasis.ResultsThere were 420 incident hospita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 23 publications
0
18
0
Order By: Relevance
“…It is interesting to note that, as found by P hua et al [ 14 ], in other studies most health expenditures related to bronchiectasis were linked to hospitalisations [ 16 , 17 ]. Despite the existence of variability in the rate of hospitalisation related to bronchiectasis between countries, the impact of this condition on health systems is unquestionable.…”
mentioning
confidence: 75%
See 4 more Smart Citations
“…It is interesting to note that, as found by P hua et al [ 14 ], in other studies most health expenditures related to bronchiectasis were linked to hospitalisations [ 16 , 17 ]. Despite the existence of variability in the rate of hospitalisation related to bronchiectasis between countries, the impact of this condition on health systems is unquestionable.…”
mentioning
confidence: 75%
“…This is a relevant topic since not every finding can be promptly extrapolated to the reality of other populations. In this study by P hua et al [ 14 ], they found a decline in the age-standardised incidence of hospitalised bronchiectasis over time. One of the reasons attributed by the authors for this finding was the significant reduction in tuberculosis cases in Singapore in recent years [ 14 ], since Mycobacterium tuberculosis infection is a well-recognised cause of bronchiectasis.…”
mentioning
confidence: 84%
See 3 more Smart Citations